La convención Belém Do Pará un balance de su aplicación en la jurisprudencia de la Corte Interamericana, a 16 años de su entrada en vigor. (2011)
This article is presented as a result of an investigation that had the object to know the cases which the Inter-American Court of human Rights applied The Inter-American Convention on the prevention; punishment and eradication of violence against women Convention of Belém in its contentious function; when in the cases found factual situations violence against women.